2018
DOI: 10.1007/s00773-018-0573-z
|View full text |Cite
|
Sign up to set email alerts
|

Engineering analysis of turbulent flow measurements near Kuchinoshima Island

Abstract: Ocean current measurements from near Kuchinoshima Island are analyzed to consider turbulence characteristics with regard to the engineering design of an ocean current turbine. The location of the measurements is offshore of Kuchinoshima in the Tokara Strait within the path of the Kuroshio Current. The measurement campaign was from January 15 to 16, 2016 using the Nortek Signature 500 ADCP and Nortek Vector ADV. Turbulence characteristics of turbulence intensity, integral timescale, and integral length scale ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Similar phenomenon was also reported by Novo and Kyozuka 51 in a field study at a natural channel under the tidal current flow conditions. Recently in the study of Imamura et al,52 similar pattern of autocorrelation function was reported. The autocorrelation function estimation locations, y/B = 0.02, 0.1, 0.5 and 1 represent the region close to the wall, mid-region and far-region from the wall.…”
supporting
confidence: 76%
“…Similar phenomenon was also reported by Novo and Kyozuka 51 in a field study at a natural channel under the tidal current flow conditions. Recently in the study of Imamura et al,52 similar pattern of autocorrelation function was reported. The autocorrelation function estimation locations, y/B = 0.02, 0.1, 0.5 and 1 represent the region close to the wall, mid-region and far-region from the wall.…”
supporting
confidence: 76%
“…5 Since 2011, development of a single point moored, floating, twin turbine has been underway to harness the energy of the Kuroshio Current and various elements of the flow conditions have been studied. 6,7 The device design being considered in this work is meant to operate submerged in the midwater column utilizing large ;15 m diameter turbine blades. This small size ocean current turbine is estimated to generate about 200 kW, suitable for a small demand load, such as that of a small remote island.…”
Section: Introductionmentioning
confidence: 99%
“…If the ADCP could accurately capture other turbulence quantities, such as Reynolds stress (e.g., or turbulent kinetic energy (e.g., Imamura et al, 2018;, the transverse mixing coefficient could potentially be extracted as well by combining measurements with additional information on the water body. Methods for calculating turbulent kinetic energy (TKE) from an ADCP in literature (1) make assumptions regarding the flow (e.g., , (2) position the ADCP or ADCPs strategically with certain beam sets (e.g., Guerra and Thompson, 2017;Imamura et al, 2018), or (3) measure not the true value of TKE but indicate the relative strength of turbulence in the water column (e.g., . A method that is simple to apply, can be used with any ADCP, and produces accurate estimates of TKE would be useful in predicting mixing and transport in rivers.…”
Section: Chapter 1 General Introduction Significance and Problem Defi...mentioning
confidence: 99%
“…Reynolds stresses have been used to assess performances of stream barbs and estimate eddy diffusivities and mixing times in a coastal river . Turbulent kinetic energy (TKE) is also important for several applications, such as modeling turbulence in tidal currents (Garcia Novo and Kyozuka, 2020), characterizing mixing for invasive species control in a large lake , and measuring anticipated tidal energy for turbine design (Imamura et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation